Preparation method of a photocatalytic antibacterial spray for skin wound infection, product and application thereof

CN119499370BActive Publication Date: 2026-10-09CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411421914.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2026-10-09
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

[0003]尽管目前很多皮肤敷料如纱布、医用棉已经应用到临床上作为治疗方法,但它们对于伤口愈合的刺激作用不明显,治疗效果并不理想

Benefits of technology

[0022] The beneficial effects of this invention are as follows: This invention discloses a photocatalytic antibacterial spray for skin wound infection and its preparation method. It mainly uses natural polysaccharides and ZIF-8@H-MPB composite nanoparticles (ZHP) to prepare a photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray). This multifunctional skin dressing possesses antibacterial, wound-healing-promoting, sunlight-triggered, and real-time monitoring properties, and has both monitoring and treatment functions. On the one hand, when the spray is applied to the wound, it adheres to the skin surface, forming a protective film covering the wound, effectively reducing external irritation to the wound. The Zn released by the nanoparticles... 2+It promotes wound healing and regeneration. At the same time, ZIF-8@H-MPB nanoparticles generate ROS under the trigger of sunlight to enhance antibacterial ability, which can effectively treat wound infection. On the other hand, the metabolic process of bacteria affects the redox reaction of Prussian blue, producing visible optical changes, thereby achieving the monitoring effect. The dressing can also be changed regularly according to the color change of the dressing. In addition, the photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection disclosed in this invention has the following advantages: (1) The optical changes generated by the reduction reaction between Prussian blue nanoparticles (PB) and bacterial metabolism during the preparation process realize the dynamic monitoring of the antibacterial process; (2) The spray form prepared can better adapt to irregular wound shapes compared with traditional dressings such as hydrogel and gauze; (3) The prepared antibacterial spray uses sunlight to generate ROS to achieve efficient antibacterial effect. The zinc ions released by the nanoparticles form metal coordination bonds with the oxidized bacterial cellulose to improve its mechanical properties after film formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499370B_ABST
    Figure CN119499370B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method of a photocatalytic antibacterial spray for skin wound infection, a product and application thereof, and belongs to the technical field of antibacterial material preparation. The photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection disclosed in the application has the following advantages: (1) the optical change generated by the reduction reaction of Prussian blue nanoparticles (PB) and bacterial metabolism in the preparation process realizes dynamic monitoring of the antibacterial process; (2) the prepared spray can better adapt to the irregular shape of a wound compared with traditional dressings such as hydrogel and gauze; (3) the prepared antibacterial spray realizes efficient antibiosis by using sunlight to generate ROS, and the metal coordination bond formed by the zinc ions released by the nanoparticles and the oxidized bacterial cellulose improves the mechanical properties of the film after film formation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of antibacterial material preparation technology, and relates to a preparation method of a photocatalytic antibacterial spray for skin wound infection, as well as its product and application. Background Technology

[0002] Looking at the global trend of medical dressing development, the downstream market is increasingly demanding multifunctional, new material, and high-value-added medical dressings, with more and more traditional cotton gauze being replaced by new, high-end medical dressings. Wound dressings play a significant role in the wound healing process, mainly by covering damaged skin, maintaining the necessary moist environment and suitable temperature for healing, providing physical and microbial protection, absorbing excess tissue fluid, and relieving pain. The surface design of antibacterial materials generally focuses on key factors that resist bacterial adhesion, resisting various effects of biofilms, and employing strategies such as long-lasting antifouling, intelligent self-cleaning, triggered killing, bacterial capture, and bacterial targeting. Based on materials, dressings can be categorized into gauze dressings, membrane dressings, foam dressings, adhesive tape dressings, and hydrogel dressings.

[0003] Although many skin dressings, such as gauze and medical cotton, are currently used clinically as treatment methods, their stimulating effect on wound healing is not significant, and the treatment effect is not ideal. While various antibacterial dressings are now used clinically, the diversity and complexity of skin wound shapes make it difficult to form dressings that conform to the desired shape and have good adhesion. Hydrogels may also adhere to certain wounds, making them prone to damaging the surrounding delicate skin when removed. The application of antibacterial dressings such as hydrogels and gauze is particularly hindered for large and irregular wounds.

[0004] Skin damage makes it susceptible to bacterial invasion, making wound infection monitoring crucial. Traditional methods for monitoring skin wounds are not only time-consuming but also limited by the available instruments. Therefore, it is essential to develop an antibacterial spray that can adapt to different skin wounds, visualize wound healing, effectively kill bacteria, and provide real-time monitoring of bacterial infection.

[0005] Natural polysaccharides exhibit better biocompatibility and can form denser structures through cross-linking. Chitosan, sodium alginate, and cellulose are also frequently used in the preparation of wound dressings. Furthermore, Prussian blue nanoparticles (PB) can act as "indicators" in materials, using color changes to determine the timing of dressing changes and the status of wound infection. On the other hand, PB not only possesses photothermal properties but also exhibits POD enzyme activity under acidic conditions and CAT and SOD enzyme activities under neutral and alkaline conditions. Therefore, modifying PB into a hollow mesoporous structure increases its surface area, enhances light reflection, increases its enzyme-like activity, and reduces ROS generated by ZIF-8 during antibacterial processes. Using hollow mesoporous Prussian blue (H-MPB) as a photothermal promoter coupled with ZIF-8 allows the material to utilize solar radiation to enhance its antibacterial effect. Meanwhile, the release of zinc ions can not only promote fibroblast migration, angiogenesis, collagen deposition and granulation tissue formation, and accelerate wound healing, but also form metal coordination bonds with the carboxyl groups in oxidized BC, thereby increasing the degree of cross-linking of the composite membrane.

[0006] In summary, this further research expands the application of PB color indicators in the biomedical field. Furthermore, the nanoparticles formed by the coupling of H-MPB and ZIF-8 can generate photothermal effects under sunlight, enhancing antibacterial capabilities. This provides a novel and promising strategy for the diagnosis and treatment of bacterial wound infections, exhibiting good tissue penetration depth and low side effects, reducing the overuse of antibiotics in wound infection treatment. Simultaneously, it endows the material with dynamic monitoring capabilities, promotes wound healing, and possesses good biocompatibility and antibacterial properties. Summary of the Invention

[0007] In view of this, one objective of the present invention is to provide a photocatalytic antibacterial spray for skin wound infection; a second objective of the present invention is to provide a method for preparing the photocatalytic antibacterial spray for skin wound infection; and a third objective of the present invention is to provide an application of the photocatalytic antibacterial spray for skin wound infection in the antibacterial and repair aspects of skin wounds.

[0008] To achieve the above objectives, the present invention provides the following technical solution:

[0009] 1. A method for preparing a photocatalytic antibacterial spray for skin wound infection, the preparation method comprising the following steps:

[0010] A carboxyl-activated solution was obtained by stirring a TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), and N-hydroxysuccinimide (NHS) at room temperature. An acetic acid solution of natural polysaccharides was then added, and the mixture was stirred at room temperature for 18–24 h to form a BC-CS solution. After the reaction was completed, the mixture was dialyzed, and the ZIF-8@H-MPB composite nanoparticles (ZHP) prepared in step (2) were added. The mixture was stirred at room temperature overnight to prepare a photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray).

[0011] Preferably, the ZIF-8@H-MPB composite nanoparticles (ZHP) are prepared according to the following method:

[0012] (1) Preparation of hollow mesoporous Prussian blue nanoparticles (H-MPB): Polyvinylpyrrolidone (PVP) and potassium ferricyanide trihydrate were added to hydrochloric acid solution and stirred to dissolve them to form a clear and transparent mixed solution. After heating and reaction, Prussian blue nanoparticles (PB) were obtained by centrifugation. PPB was then mixed with polyvinylpyrrolidone (PVP) and stirred to dissolve in hydrochloric acid solution. After heating and reaction, PPB was centrifuged and washed to obtain hollow mesoporous Prussian blue nanoparticles (H-MPB).

[0013] (2) Preparation of ZIF-8@H-MPB composite nanoparticles (ZHP): Polyvinylpyrrolidone (PVP) was dissolved in methanol, and then the hollow mesoporous Prussian blue nanoparticles (H-MPB) prepared in step (1) were added. After stirring to disperse them evenly, zinc nitrate hexahydrate and 2-methylimidazole (2-Mel) were added. After stirring for 6 to 12 hours, the mixture was centrifuged and washed to obtain ZIF-8@H-MPB composite nanoparticles (ZHP).

[0014] More preferably, in step (1), the mass molar ratio of polyvinylpyrrolidone (PVP) to potassium ferricyanide trihydrate is 7.5:1 (g:mmol), and the mass ratio of Prussian blue nanoparticles (PB) to polyvinylpyrrolidone (PVP) is 1:5.

[0015] More preferably, in step (1), the heating reaction during the preparation of Prussian blue nanoparticles (PB) is carried out at a temperature of 80°C for 20 hours, and the reaction between Prussian blue nanoparticles (PB) and polyvinylpyrrolidone (PVP) is carried out at a temperature of 140°C for 4 hours.

[0016] More preferably, in step (2), the mass ratio of polyvinylpyrrolidone (PVP), hollow mesoporous Prussian blue nanoparticles (H-MPB), zinc nitrate hexahydrate and 2-methylimidazole (2-Mel) is 60:8:12.8 to 25.6:3.5.

[0017] Preferably, the mass ratio of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), and N-hydroxysuccinimide (NHS) in the carboxyl-activated solution is 16:228.2:112.79.

[0018] Preferably, the volume-to-mass ratio of the natural polysaccharide and the ZIF-8@H-MPB composite nanoparticles (ZHP) in the carboxyl-activated solution, the chitosan (CS) acetic acid solution, and the composite nanoparticles is 100–120:0.5–2:1 x 10⁻⁶. -4 ~5x10 -4 , ml:g:g.

[0019] Preferably, the natural polysaccharide is any one or both of bacterial cellulose or chitosan (CS).

[0020] 2. The photocatalytic antibacterial spray for skin wound infection prepared by the above preparation method.

[0021] 3. The application of the above-mentioned photocatalytic antibacterial spray for skin wound infection in antibacterial and repair functions of skin wounds.

[0022] The beneficial effects of this invention are as follows: This invention discloses a photocatalytic antibacterial spray for skin wound infection and its preparation method. It mainly uses natural polysaccharides and ZIF-8@H-MPB composite nanoparticles (ZHP) to prepare a photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray). This multifunctional skin dressing possesses antibacterial, wound-healing-promoting, sunlight-triggered, and real-time monitoring properties, and has both monitoring and treatment functions. On the one hand, when the spray is applied to the wound, it adheres to the skin surface, forming a protective film covering the wound, effectively reducing external irritation to the wound. The Zn released by the nanoparticles... 2+It promotes wound healing and regeneration. At the same time, ZIF-8@H-MPB nanoparticles generate ROS under the trigger of sunlight to enhance antibacterial ability, which can effectively treat wound infection. On the other hand, the metabolic process of bacteria affects the redox reaction of Prussian blue, producing visible optical changes, thereby achieving the monitoring effect. The dressing can also be changed regularly according to the color change of the dressing. In addition, the photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection disclosed in this invention has the following advantages: (1) The optical changes generated by the reduction reaction between Prussian blue nanoparticles (PB) and bacterial metabolism during the preparation process realize the dynamic monitoring of the antibacterial process; (2) The spray form prepared can better adapt to irregular wound shapes compared with traditional dressings such as hydrogel and gauze; (3) The prepared antibacterial spray uses sunlight to generate ROS to achieve efficient antibacterial effect. The zinc ions released by the nanoparticles form metal coordination bonds with the oxidized bacterial cellulose to improve its mechanical properties after film formation.

[0023] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description

[0024] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein:

[0025] Figure 1 In the comparative example, A represents the tensile properties of different BC-CS composite films after film formation, and B represents the tensile properties of chitosan (CS), the photocatalytic antibacterial spray for skin wound infection prepared in Example 1 (BC-CS@ZHP antibacterial spray), and the BC-CS composite film (BC-CS) prepared in Comparative Example 2 after film formation.

[0026] Figure 2 To compare the adhesion properties of different BC-CS composite films prepared in Examples 1-3 after film formation;

[0027] Figure 3 To compare the swelling properties of different BC-CS composite films prepared in Examples 1-3 after film formation;

[0028] Figure 4 The antibacterial properties of ZIF-8@H-MPB composite nanoparticles (ZHP) and hollow mesoporous Prussian blue (H-MPB) prepared in Example 1 at different concentrations under visible light;

[0029] Figure 5 To compare the color indication effect of the modified H-MPB nanoparticles (BC-CS@HP) prepared in Example 4 and the photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray) in Example 3 after film formation. Detailed Implementation

[0030] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Unless otherwise specified, the following embodiments and features can be combined with each other.

[0031] Example 1

[0032] A photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection is prepared as follows:

[0033] (1) Preparation of hollow mesoporous Prussian blue nanoparticles (H-MPB): 7.5g of polyvinylpyrrolidone (PVP) and 329.25mg of potassium ferricyanide trihydrate were added to 100ml of hydrochloric acid solution and stirred to dissolve and form a clear and transparent mixed solution. The mixture was heated to 80℃ and reacted for 20h. After centrifugation, Prussian blue nanoparticles (PB) were obtained. 0.02g of Prussian blue nanoparticles (PB) were weighed and mixed with 0.1g of polyvinylpyrrolidone (PVP) and stirred to dissolve in 20ml of hydrochloric acid solution. The mixture was heated to 140℃ and reacted for 4h. After centrifugation and washing, hollow mesoporous Prussian blue nanoparticles (H-MPB) were obtained.

[0034] (2) Preparation of ZIF-8@H-MPB composite nanoparticles (ZHP): 60 mg of polyvinylpyrrolidone (PVP) was dissolved in 12 ml of methanol, and then 8 mg of hollow mesoporous Prussian blue nanoparticles (H-MPB) prepared in step (1) was added. After stirring to disperse them evenly, 12.8 g of zinc nitrate hexahydrate and 3.5 g of 2-methylimidazolium (2-Mel) were added. After stirring for 6 h, the mixture was centrifuged and washed to obtain ZIF-8@H-MPB composite nanoparticles (ZHP) (see the specific reference Prussian Blue@Zeolitic imidazolate framework composite toward solar-triggered biodecontamination, Chemical Engineering Journal 452(2023)138562);

[0035] (3) Preparation of photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray): 0.016g of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 228.2mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), and 112.79mg of N-hydroxysuccinimide (NHS) were added and stirred at room temperature to obtain carboxyl-activated powder. An acetic acid solution of natural polysaccharide (containing 1g of bacterial cellulose and 1g of polysaccharide (CS)) was added, and the mixture was stirred overnight at room temperature to form a BC-CS solution. After the reaction was complete, the solution was dialyzed, and 1x10⁻⁶ ppm was added. -4 The ZIF-8@H-MPB composite nanoparticles (ZHP) prepared in step (2) are doped and stirred overnight at room temperature. The zinc ions released by the ZIF-8@H-MPB composite nanoparticles (ZHP) undergo a cross-linking reaction with the oxidized carboxyl groups in bacterial cellulose. After drying at room temperature, a photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) with a porous membrane structure for skin wound infection can be prepared.

[0036] Example 2

[0037] A photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection is prepared as follows:

[0038] (1) Preparation of hollow mesoporous Prussian blue nanoparticles (H-MPB): 7.5g of polyvinylpyrrolidone (PVP) and 329.25mg of potassium ferricyanide trihydrate were added to 100ml of hydrochloric acid solution and stirred to dissolve and form a clear and transparent mixed solution. The mixture was heated to 80℃ and reacted for 20h. After centrifugation, Prussian blue nanoparticles (PB) were obtained. 0.02g of Prussian blue nanoparticles (PB) were weighed and mixed with 0.1g of polyvinylpyrrolidone (PVP) and stirred to dissolve in 20ml of hydrochloric acid solution. The mixture was heated to 140℃ and reacted for 4h. After centrifugation and washing, hollow mesoporous Prussian blue nanoparticles (H-MPB) were obtained.

[0039] (2) Preparation of ZIF-8@H-MPB composite nanoparticles (ZHP): 60 mg of polyvinylpyrrolidone (PVP) was dissolved in 12 ml of methanol, and then 8 mg of hollow mesoporous Prussian blue nanoparticles (H-MPB) prepared in step (1) was added. After stirring to disperse them evenly, 20 g of zinc nitrate hexahydrate and 3.5 g of 2-methylimidazolium (2-Mel) were added. After stirring for 8 h, the mixture was centrifuged and washed to obtain ZIF-8@H-MPB composite nanoparticles (ZHP) (see the reference Prussian Blue@Zeolitic imidazolate framework composite toward solar-triggered biodecontamination, Chemical Engineering Journal 452 (2023) 138562).

[0040] (3) Preparation of photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray): 0.016g of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 228.2mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), and 112.79mg of N-hydroxysuccinimide (NHS) were added and stirred at room temperature to obtain carboxyl-activated powder. An acetic acid solution of natural polysaccharide (containing 1g of bacterial cellulose and 1g of polysaccharide (CS)) was added, and the mixture was stirred at room temperature for 18h to form a BC-CS solution. After the reaction was completed, the solution was dialyzed, and 1x10⁻⁶ ppm was added. -4 The ZIF-8@H-MPB composite nanoparticles (ZHP) prepared in step (2) are doped and stirred overnight at room temperature. The zinc ions released by the ZIF-8@H-MPB composite nanoparticles (ZHP) undergo a cross-linking reaction with the oxidized carboxyl groups in bacterial cellulose. After drying at room temperature, a photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) with a porous membrane structure for skin wound infection can be prepared.

[0041] Example 3

[0042] A photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection is prepared as follows:

[0043] (1) Preparation of hollow mesoporous Prussian blue nanoparticles (H-MPB): 7.5g of polyvinylpyrrolidone (PVP) and 329.25mg of potassium ferricyanide trihydrate were added to 100ml of hydrochloric acid solution and stirred to dissolve and form a clear and transparent mixed solution. The mixture was heated to 80℃ and reacted for 20h. After centrifugation, Prussian blue nanoparticles (PB) were obtained. 0.02g of Prussian blue nanoparticles (PB) were weighed and mixed with 0.1g of polyvinylpyrrolidone (PVP) and stirred to dissolve in 20ml of hydrochloric acid solution. The mixture was heated to 140℃ and reacted for 4h. After centrifugation and washing, hollow mesoporous Prussian blue nanoparticles (H-MPB) were obtained.

[0044] (2) Preparation of ZIF-8@H-MPB composite nanoparticles (ZHP): 60 mg of polyvinylpyrrolidone (PVP) was dissolved in 12 ml of methanol, and then 8 mg of hollow mesoporous Prussian blue nanoparticles (H-MPB) prepared in step (1) was added. After stirring to disperse them evenly, 25.6 g of zinc nitrate hexahydrate and 3.5 g of 2-methylimidazolium (2-Mel) were added. After stirring for 12 h, the mixture was centrifuged and washed to obtain ZIF-8@H-MPB composite nanoparticles (ZHP) (see the reference Prussian Blue@Zeolitic imidazolate framework composite toward solar-triggered biodecontamination, Chemical Engineering Journal 452(2023)138562).

[0045] (3) Preparation of photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray): 0.016g of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 228.2mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), and 112.79mg of N-hydroxysuccinimide (NHS) were added and stirred at room temperature to obtain carboxyl-activated powder. An acetic acid solution of natural polysaccharide (containing 1g of bacterial cellulose and 1g of polysaccharide (CS)) was added, and the mixture was stirred at room temperature for 24h to form a BC-CS solution. After the reaction was completed, the solution was dialyzed, and 1x10⁻⁶ ppm was added. -4The ZIF-8@H-MPB composite nanoparticles (ZHP) prepared in step (2) are doped and stirred overnight at room temperature. The zinc ions released by the ZIF-8@H-MPB composite nanoparticles (ZHP) undergo a cross-linking reaction with the oxidized carboxyl groups in bacterial cellulose. After drying at room temperature, a photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) with a porous membrane structure for skin wound infection can be prepared.

[0046] Comparative Example 1

[0047] A BC-CS composite membrane (0.33% BC:CS) is prepared by the following method:

[0048] 0.016 g of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 228.2 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), and 112.79 mg of N-hydroxysuccinimide (NHS) were added and stirred at room temperature to obtain carboxyl-activated powder. An acetic acid solution of natural polysaccharide (containing 1 g of bacterial cellulose and 0.5 g of chitosan (CS) mixed via an amide reaction) was added and stirred overnight at room temperature to form a BC-CS solution. After the reaction was completed, the solution was dialyzed, stirred overnight at room temperature, and dried at room temperature to prepare a BC-CS composite membrane (0.33% BC:CS).

[0049] Comparative Example 2

[0050] A BC-CS composite membrane (0.67% BC:CS) is prepared by the following method:

[0051] In Comparative Example 1, the phrase "1g of bacterial cellulose and 0.5g of chitosan (CS) in an acetic acid solution of natural polysaccharides are mixed via an amide reaction" is modified to "1g of bacterial cellulose and 1g of chitosan (CS) in an acetic acid solution of natural polysaccharides are mixed via an amide reaction". The rest is the same as in Comparative Example 1.

[0052] Comparative Example 3

[0053] A BC-CS composite membrane (1.33% BC:CS) is prepared by the following method:

[0054] The phrase "1g of bacterial cellulose and 0.5g of chitosan (CS) in the acetic acid solution of natural polysaccharides are mixed by an amide reaction" in Comparative Example 1 is modified to "1g of bacterial cellulose and 2g of chitosan (CS) in the acetic acid solution of natural polysaccharides are mixed by an amide reaction", and the rest is the same as in Comparative Example 1.

[0055] Comparative Example 4

[0056] A BC-CS@HP antibacterial spray, the specific preparation method of which is shown below:

[0057] (1) Preparation of hollow mesoporous Prussian blue nanoparticles (H-MPB): 7.5g of polyvinylpyrrolidone (PVP) and 329.25mg of potassium ferricyanide trihydrate were added to 100ml of hydrochloric acid solution and stirred to dissolve and form a clear and transparent mixed solution. The mixture was heated to 80℃ and reacted for 20h. After centrifugation, Prussian blue nanoparticles (PB) were obtained. The mixture was then mixed with 0.1g of polyvinylpyrrolidone (PVP) and stirred to dissolve in 20ml of hydrochloric acid solution. The mixture was heated to 140℃ and reacted for 4h. After centrifugation and washing, hollow mesoporous Prussian blue nanoparticles (H-MPB) were obtained.

[0058] (2) Preparation of BC-CS@HP: 0.016 g of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 228.2 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), and 112.79 mg of N-hydroxysuccinimide (NHS) were added and stirred at room temperature to obtain carboxyl-activated powder. An acetic acid solution of natural polysaccharides (containing 0.67 g of bacterial cellulose and 1.33 g of polysaccharide (CS) mixed via an amide reaction) was added, and the mixture was stirred overnight at room temperature to form a BC-CS solution. After the reaction was complete, the solution was dialyzed, and 1 x 10⁻⁶ ppm was added. -5 The hollow mesoporous Prussian blue nanoparticles (H-MPB) prepared in step (1) are doped and stirred overnight at room temperature to obtain BC-CS@HP antibacterial spray doped with hollow mesoporous Prussian blue nanoparticles (H-MPB).

[0059] Performance testing

[0060] Figure 1 In Figure A, the tensile properties of different BC-CS composite films prepared in the comparative examples are shown after film formation. Figure B shows the tensile properties of chitosan (CS), the photocatalytic antibacterial spray for skin wound infection prepared in Example 1 (BC-CS@ZHP antibacterial spray), and the BC-CS composite film (BC-CS) prepared in Comparative Example 2 after film formation. Figure 1As shown in Figure A, tensile fracture tests were conducted on BC-CS composite films with three different chitosan ratios. The stress-strain curves revealed that while the 0.33% BC-CS composite film exhibited higher stress, its elongation at fracture was zero, indicating relative brittleness. The 0.67% BC-CS composite film achieved a stress of 52.58 kPa and demonstrated good ductility. The 1.33% BC-CS composite film showed a stress of only 12.75 kPa, and its fracture strain was also lower than that of the 0.67% BC-CS composite film. Therefore, considering all three chitosan ratios, the 0.67% BC-CS composite film demonstrated better tensile strength. Furthermore, while CS exhibited high stress, its fracture strain was poor. Compared to pure CS, the addition of bacterial cellulose (BC), although reducing the stress to 24.30 kPa, effectively improved the ductility of the composite film. The addition of ZHP nanoparticles released some zinc ions, further promoting the cross-linking degree of the BC-CS film and thus enhancing its tensile properties.

[0061] Figure 2 To compare the adhesion properties of the different BC-CS composite films prepared in Examples 1-3 after film formation. From Figure 2 It can be seen that the adhesion properties between the BC-CS composite film and pigskin with different proportions show that the adhesion force between the 0.67% BC-CS composite film and pigskin can reach up to 22.08 kPa. This result further verifies that the 0.67% BC-CS composite film has a better cross-linking effect and better mechanical properties.

[0062] Figure 3 To compare the swelling properties of different BC-CS composite films prepared in Examples 1-3 after film formation. From Figure 3 It can be seen that the swelling rate of 1.33% BC-CS can reach 326.45%, proving that the material has a certain swelling rate, which can ensure the absorption of wound exudate while avoiding membrane damage.

[0063] Figure 4 The antibacterial properties of ZIF-8@H-MPB composite nanoparticles (ZHP) and hollow mesoporous Prussian blue (H-MPB) prepared in Example 1 at different concentrations under visible light were compared. Figure 4 It can be seen that ZIF-8@H-MPB composite nanoparticles (ZHP) already have excellent antibacterial properties at a nanoparticle concentration of 300 μg / mL, and their antibacterial rate can reach 99.86% under visible light.

[0064] Figure 5 To compare the color indication effect of the modified H-MPB nanoparticles (BC-CS@HP) prepared in Example 4 and the photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray) in Example 3 after film formation. Figure 5It can be seen that both the modified H-MPB nanoparticles and the photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray) have color indication capabilities and can undergo a reduction reaction with bacterial metabolism to be reduced to white.

[0065] In addition, the same performance tests were performed on the photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection prepared in Examples 2 and 3 above. The results were similar to those of the photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection in Example 1. Both have good antibacterial and wound healing capabilities, and are multifunctional skin dressings that can be triggered by sunlight and monitored in real time, with dual functions of monitoring and treatment.

[0066] In summary, this invention discloses a photocatalytic antibacterial spray for skin wound infection and its preparation method. It mainly uses natural polysaccharides and ZIF-8@H-MPB composite nanoparticles (ZHP) to prepare a photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray). This multifunctional skin dressing possesses antibacterial, wound-healing-promoting, sunlight-triggered, and real-time monitoring properties, exhibiting both monitoring and therapeutic functions. On one hand, when the spray is applied to the wound, it adheres to the skin surface, forming a protective film covering the wound, effectively reducing external irritation. The nanoparticles release Zn... 2+ It promotes wound healing and regeneration. At the same time, ZIF-8@H-MPB nanoparticles generate ROS under the trigger of sunlight to enhance antibacterial ability, which can effectively treat wound infection. On the other hand, the metabolic process of bacteria affects the redox reaction of Prussian blue, producing visible optical changes, thereby achieving the monitoring effect. The dressing can also be changed regularly according to the color change of the dressing. In addition, the photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection disclosed in this invention has the following advantages: (1) The optical changes generated by the reduction reaction between Prussian blue nanoparticles (PB) and bacterial metabolism during the preparation process realize the dynamic monitoring of the antibacterial process; (2) The spray form prepared can better adapt to irregular wound shapes compared with traditional dressings such as hydrogel and gauze; (3) The prepared antibacterial spray uses sunlight to generate ROS to achieve efficient antibacterial effect. The zinc ions released by the nanoparticles form metal coordination bonds with the oxidized bacterial cellulose to improve its mechanical properties after film formation.

[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. The application of a photocatalytic antibacterial spray for skin wound infection in the preparation of antibacterial and repairing agents for skin wounds, characterized in that, The preparation method of the photocatalytic antibacterial spray for skin wound infection includes the following steps: (1) Preparation of hollow mesoporous Prussian blue nanoparticles: 7.5g of polyvinylpyrrolidone (PVP) and 329.25mg of potassium ferricyanide trihydrate were added to 100ml of hydrochloric acid solution and stirred to dissolve and form a clear and transparent mixed solution. The mixture was heated to 80℃ and reacted for 20h. After centrifugation, Prussian blue nanoparticles (PB) were obtained. 0.02g of Prussian blue nanoparticles (PB) were weighed and mixed with 0.1g of polyvinylpyrrolidone (PVP) and stirred to dissolve in 20ml of hydrochloric acid solution. The mixture was heated to 140℃ and reacted for 4h. After centrifugation and washing, hollow mesoporous Prussian blue nanoparticles (H-MPB) were obtained. (2) Preparation of ZIF-8@H-MPB composite nanoparticles: 60 mg of polyvinylpyrrolidone (PVP) was dissolved in 12 ml of methanol, and then 8 mg of hollow mesoporous Prussian blue nanoparticles (H-MPB) prepared in step (1) was added. After stirring to disperse them evenly, 12.8 g of zinc nitrate hexahydrate and 3.5 g of 2-methylimidazole (2-Mel) were added. After stirring for 6 h, the mixture was centrifuged and washed to obtain ZIF-8@H-MPB composite nanoparticles (ZHP). (3) Preparation of a photocatalytic antibacterial spray for skin wound infection: 0.016 g of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 228.2 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), and 112.79 mg of N-hydroxysuccinimide (NHS) were stirred at room temperature to obtain carboxyl-activated powder. An acetic acid solution of natural polysaccharide containing 1 g of bacterial cellulose and 1 g of chitosan (CS) was added. The mixture was stirred overnight at room temperature to form a BC-CS solution. After the reaction was completed, the solution was dialyzed, and 1 x 10⁻⁶ g of chitosan was added. -4 The ZIF-8@H-MPB composite nanoparticles (ZHP) prepared in step (2) are doped and stirred overnight at room temperature. The zinc ions released by the ZIF-8@H-MPB composite nanoparticles (ZHP) undergo a cross-linking reaction with the oxidized carboxyl groups in bacterial cellulose. After drying at room temperature, a photocatalytic antibacterial spray for skin wound infection can be prepared.

2. The photocatalytic antibacterial spray for skin wound infection prepared according to claim 1.